2017
DOI: 10.21608/jssae.2017.38089
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of Nitrogen Fertilizer Forms, Irrigation Intervals and Soil Conditioners on Maize Productivity Grown on Clay Loam Soil.

Abstract: Maize is the third important cereal crop in Egypt after wheat and rice. Injection of ammonia gas as a nitrogen fertilizer is used widely comparable with other nitrogen fertilizer forms due to the high nitrogen content (82 %) as well as its cheapest price. Two field trials were carried out at Tameia Agricultural Research Station, Fayoum Governorate, Egypt during 2014 and 2015 summer seasons to study the effect of nitrogen fertilization forms (ammonia gas 82 N% and ammonium nitrate 33.5N%), irrigation intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
3
2
0
Order By: Relevance
“…Increasing irrigation intervals up to 15 days will decrease the soil moisture availability in the root zone, which in turn decrease vegetative growth of corn plant and dry matter accumulation during filling of grains, as well as reducing nutrients absorption from soil. Similar results were reported by Abo-Marzoka et al, 2016;Abdou et al, 2017 andMajid et al, 2017. Table 4.…”
Section: Yield Attributedsupporting
confidence: 89%
See 2 more Smart Citations
“…Increasing irrigation intervals up to 15 days will decrease the soil moisture availability in the root zone, which in turn decrease vegetative growth of corn plant and dry matter accumulation during filling of grains, as well as reducing nutrients absorption from soil. Similar results were reported by Abo-Marzoka et al, 2016;Abdou et al, 2017 andMajid et al, 2017. Table 4.…”
Section: Yield Attributedsupporting
confidence: 89%
“…In addition, the calculation of the gathered data reveals that the values of the above contents significantly varied within the irrigation treatments. Similar results were obtained by Abo-Marzoka et al, 2016;Abdou et al, 2017 andMajid et al, 2017. A highly significant interaction between N-fertilizer in absence and presence of proline, plant distance and irrigation intervals affected the concentration of N, P and K and proline content in leaves of maize plant. During the season the treatment of 150 N-fertilization in presence of proline + 15 cm spacing and 10 days' intervals maintained significantly higher N, P and K concentrations as well as proline content than other treatments as shown in Fig 3.…”
Section: Chlorophyll Contentsupporting
confidence: 87%
See 1 more Smart Citation
“…Ismail el al., (2013) found that the application of AA at high rate led to increase of plant characters. Abdou et al (2017) concluded that the highest mean values of maize grain yield and its components were linked to AA, which increased grain yield by 4-6% in the two successive seasons, respectively, compared to those obtained by AN.…”
Section: Agronomic Traits Grain Yield and Yield Components: Effect Omentioning
confidence: 90%
“…Yield and its components increased by using AA as compared with urea or other nitrogen fertilizer sources (Darwish, 2003 andSiam et al, 2008). The highest averages values of yield and its components and the highest averages of N, P and K concentration in maize plants and their uptake in grains were resulted from injection of ammonia gas (Abdou et al 2017). Application of AA gave the highest recorded values of NPK concentrations in grain, stover yields and also its uptake by plants than urea fertilizer (Siam et al, 2008 andAbd El-Hafeez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%